Biorefinery process for production of bioactive compounds and bio-oil from Camellia oleifera shell - Wang, Yunpu; Ke, Linyao; Yang, Qi; Peng, Yujie; Hu, Yanzhe; Dai, Leilei; Jiang, Lin; Wu, Qiuhao; Liu, Yuhuan; Ruan, Roger; Fu, Guiming (International Journal of Agricultural and Biological Engineering, 2019)
A biorefinery process was developed in this study to obtain bioactive compounds and bio-oil from Camellia oleifera shells. Four different extraction techniques (water, ethanol, ultrasound-assisted deionized water, and ultrasound-assisted ethanol) were utilized to extract tea saponin and tannin from C. oleifera shells. Results showed that ethanol had better extraction capacity than did deionized water, and ultrasound could promote the dissolution of tannin and tea saponin in solution. The thermogravimetric curves of the samples treated under the four conditions moved toward high temperatures. This phenomenon indicated the thermal stability of the residue was significantly improved. The pretreatment showed a slight effect on the chemical compositions of bio-oil. Specifically, the samples treated with ethanol and ultrasound-assisted deionized water contained higher phenol contents (81.07% and 81.52%, respectively) than the other samples. The content of organic acid decreased with an increase in the phenol content.Keywords: Camellia oleifera shell, bio-oil, bioactive compounds, biorefinery, ultrasound-assisted extraction, pyrolysisDOI: 10.25165/j.ijabe.20191205.4593Citation: Wang Y P, Ke L Y, Yang Q, Peng Y J, Hu Y Z, Dai L L, et al. Biorefinery process for production of bioactive compounds and bio-oil from Camellia oleifera shell. Int J Agric & Biol Eng, 2019; 12(5): 190–194.